2007
DOI: 10.1038/cr.2007.112
|View full text |Cite
|
Sign up to set email alerts
|

Redox status of thioredoxin-1 (TRX1) determines the sensitivity of human liver carcinoma cells (HepG2) to arsenic trioxide-induced cell death

Abstract: Intracellular redox homeostasis plays a critical role in determining tumor cells' sensitivity to drug-induced apoptosis. Here we investigated the role of thioredoxin-1 (TRX1), a key component of redox regulation, in arsenic trioxide (As 2 O 3 )-induced apoptosis. Over-expression of wild-type TRX1 in HepG 2 cells led to the inhibition of As 2 O 3 -induced cytochrome c (cyto c) release, caspase activation and apoptosis, and down-regulation of TRX1 expression by RNAi sensitized HepG 2 cells to As 2 O 3 -induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 51 publications
0
24
1
Order By: Relevance
“…In H841 cell line model, ATO downregulated both reduced and oxidative form of Trx1 without affecting redox status. This is discrepant from previous report, which indicated that ATO could inhibit thioredoxin reductase and consequently decrease the reduced form of Trx1 (68). Although the activity or expression of thioredoxin reductase has not been measured, our findings suggest that ATO targets the total Trx1 rather than just the reduced form in H841 cells.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In H841 cell line model, ATO downregulated both reduced and oxidative form of Trx1 without affecting redox status. This is discrepant from previous report, which indicated that ATO could inhibit thioredoxin reductase and consequently decrease the reduced form of Trx1 (68). Although the activity or expression of thioredoxin reductase has not been measured, our findings suggest that ATO targets the total Trx1 rather than just the reduced form in H841 cells.…”
Section: Discussioncontrasting
confidence: 56%
“…Thioredoxin system was reported to be an important target of ATO in some cancers (26,68). In H841 cell line model, ATO downregulated both reduced and oxidative form of Trx1 without affecting redox status.…”
Section: Discussionmentioning
confidence: 99%
“…TXN is reduced by thioredoxin reductases 1 and 2 (TXNRD1, TXNRD2), and oxidized to TXNS 2 by peroxiredoxin 2 (via reduction of H 2 O 2 ). TXN are not only an antioxidant but also could influence arsenic related effects by its role in arsenic metabolism and apoptosis [28,29]. GSH is also a substrate in conjugation reactions to a number of different xenobiotics, thereby promoting their elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular events of arsenic-induced apoptosis have been associated with the redox status of thioredoxin-1 and cytochrome c, which facilitate mitochondrial permeability [7,8] . In addition, the cell cycle and its regulation play an important role in arsenic-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%